Assessment of ventricular electrical heterogeneity in left bundle branch pacing and left ventricular septal pacing by using various electrophysiological methods - Rijks, Jesse H J; Heckman, Luuk; Westra, Sjoerd; Cornelussen, Richard; Ghosh, Subham; Curila, Karol; Smisek, Radovan; Grieco, Domenico; Bressi, Edoardo; Nguyên, Uyên Châu; Lumens, Joost; van Stipdonk, Antonius M W; et al. (Journal of cardiovascular electrophysiology, 2024)
INTRODUCTION: Left bundle branch area pacing (LBBAP) comprises pacing at the left ventricular septum (LVSP) or left bundle branch (LBBP). The aim of the present study was to investigate the differences in ventricular electrical heterogeneity between LVSP, LBBP, right ventricular pacing (RVP) and intrinsic conduction with different dyssynchrony measures using the ECG, vectorcardiograpy, ECG belt, and Ultrahigh frequency (UHF-)ECG. METHODS: Thirty-seven patients with a pacemaker indication for bradycardia or cardiac resynchronization therapy underwent LBBAP implantation. ECG, vectorcardiogram, ECG belt and UHF-ECG signals were recorded during RVP, LVSP and LBBP, and intrinsic activation. QRS duration (QRSd) was measured from the ECG, QRS area was calculated from the vectorcardiogram, LV activation time (LVAT) and standard deviation of activation time (SDAT) from ECG belt and electrical dyssynchrony (e-DYS16) from UHF-ECG. RESULTS: Both LVSP and LBBP significantly reduced ventricular electrical heterogeneity as compared to underlying LBBB and RV pacing in terms of QRS area (p < .001), SDAT (p < .001), LVAT (p < .001) and e-DYS16 (p < .001). QRSd was only reduced as compared to RV pacing(p < .001). QRS area was similar during LBBP and normal intrinsic conduction, e-DYS16 was similar during LVSP and normal intrinsic conduction, whereas SDAT was similar for LVSP, LBBP and normal intrinsic conduction. For all these variables there was no significant difference between LVSP and LBBP. CONCLUSION: Both LVSP and LBBP resulted in a more synchronous LV activation than LBBB and RVP. Especially LBBP resulted in levels of LV synchrony comparable to normal intrinsic conduction.
Keywords: výsledek terapie; vektorkardiografie; Ventricular Function, Left; Cardiac Pacing, Artificial; Electrocardiography; Male; Cardiac Resynchronization Therapy; funkce levé komory srdeční; kardiostimulace umělá; Middle Aged; Ventricular Septum; bradycardia pacing; bradykardie; Heart Rate; Aged; mužské pohlaví; senioři; srdeční frekvence; conduction system pacing; Vectorcardiography; dyssynchrony; Treatment Outcome; Time Factors; senioři nad 80 let; akční potenciály; lidé; blokáda Tawarova raménka; ženské pohlaví; Action Potentials; Humans; časové faktory; Bradycardia; Bundle of His; Bundle-Branch Block; prediktivní hodnota testů; Aged, 80 and over; Electrophysiologic Techniques, Cardiac; elektrofyziologické techniky kardiologické; srdeční resynchronizační terapie; left bundle branch area pacing; Female; cardiac resynchronization therapy; Hisův svazek; lidé středního věku; Predictive Value of Tests; mezikomorová přepážka; elektrokardiografie